Does parental farm upbringing influence the risk of asthma in offspring? A three-generation study. (3rd August 2020) - Timm, Signe; Svanes, Cecilie; Frydenberg, Morten; Sigsgaard, Torben; Holm, Mathias; Janson, Christer; Bråbäck, Lennart; Campbell, Brittany; Kjaer Madsen, Marie; Jõgi, Nils Oskar; Jõgi, Rain; Schiöler, Linus; et al.
Abstract: Background: A farm upbringing has been associated with lower risk of asthma and methylation of asthma-related genes. As such, a farm upbringing has the potential to transfer asthma risk across generations, but this has never been investigated. We aimed to study the generational effects from a parental farm upbringing on offspring asthma. Methods: Our study involved three generations: 5759 participants from the European Community Respiratory Health Survey (ECRHS) study (born 1945–1971, denoted G1), their 9991 parents (G0) and their 8260 offspring (G2) participating in RHINESSA (Respiratory Health In Northern Europe, Spain and Australia). Questionnaire data were collected on G0 and G1 from G1 in 2010 and on G2 from themselves in 2013. The parental/grandparental place of upbringing was categorized: (i) both parents from farm; (ii) mother from farm, father from village/city; (iii) father from farm, mother from village/city; (iv) both parents from village or one parent from village and one from city; (v) both parents from city (reference group). Grandparental upbringing was equivalently categorized. Offspring asthma was self-reported and data were analysed using Cox-regression models with G2 age as the time scale. Results: A parental farm upbringing was not associated with offspring asthma when compared with city upbringing [hazard ratio (HR) 1.12, 95% confidence interval (CI) 0.74–1.69]. Findings remained similar when stratified by offspring upbringing and asthma phenotypes. Quantitative bias analyses showed similar estimates for alternative data sources. A grandparental farm upbringing was not associated with offspring asthma in either the maternal (HR 1.05, 95% CI 0.67–1.65) or paternal line (HR 1.02, 95% CI 0.62–1.68). Conclusions: This multigenerational analysis suggests no evidence of an association between parental/grandparental farm upbringing and offspring asthma.